Pembatalan Budaya Sebagai Ekspresi Perlawanan Publik di Ruang Digital - Mudjiyanto, Bambang; Launa; Hafzotillah; Nursyamsi; Lusianawati, Hayu (Jurnal Mahardika Adiwidia, 2025)
This study captures the phenomenon of cancel culture that afflicts Indonesian celebrities due to their behavior that is considered to violate social norms and ethics; as well as revealing the social implications faced by celebrities after they become victims of cancel culture. Using a constructivist paradigm with qualitative characteristics, this study draws research data sources from social media content and literature reviews. The results show that cancel culture is a digital culture that emphasizes the social responsibility of individuals, groups, institutions, or corporations for their actions; reflecting new dynamics in social interaction, where the collective power of netizens can impose social sanctions on celebrities. Cancel culture is not only about cancellation culture, but also a reflection of the complex relationship between public power, freedom of expression, and social ethics. By understanding cancel culture, we can prevent its negative impacts, as well as promote more effective, literate, aware, and responsible use of social media. Keywords: Cancel culture, expressions of resistance, netizen collective power, negative impact, social norms